News Briefs. (April 2016) - Unknown
Abstract : Brown‐Forman awards 1 million for Speed Art Museum. GlaxoSmithKline awards 1 million under Healthcare Innovation Awards. Wells Fargo awards 7 million for microloan program. Microsoft employees raise record 125 million in 2015. JPMorgan Chase awards 2 million to address racial wealth disparities. Bechtel to continue signature partnerships with STEM education partners. Salesforce pledges 5 million to fight AIDS. Deutsche Bank Americas Foundation awards 250, 000 for career training initiative.